American Prophet : the Life and Work of Carey McWilliams. (University of Michigan Press, 2010)
A long-overdue book on the brilliant life and career of one of our greatest public intellectuals, American Prophet will introduce Carey McWilliams to a new generation of readers. Peter Richardson's absorbing and elegantly paced book reveals a figure thoroughly engaged with the issues of his time. Deftly interweaving correspondence, diary notes, published writings, and McWilliams's own and others' observations on a colorful and influential cast of characters from Hollywood, New York, Washington, DC, and the American West, Richardson maps the evolution of McWilliams's personal and professional life. Among those making an appearance are H.L. Mencken (McWilliams's mentor and role model), Louis Adamic, John Fante, Robert Towne, Richard Nixon, Studs Terkel, J. Edgar Hoover, Arthur Schlesinger, Jr., and Joseph McCarthy. American Prophet illustrates the arc of McWilliams's life and career from his early literary journalism through his legal and political activism, his stint in state government, and his two decades as editor of the Nation. This book makes the case for McWilliams's place in the Olympian realm of our most influential and prescient political writers. Peter Richardson is the editorial director at PoliPointPress in Sausalito, California. He is the author or editor of numerous works on language, literature, and California public policy. He holds a Ph. D. in English from the University of California Berkeley.